Combination of morphological characters and ITS-sequence to characterize a new species of Macrocheles (Acari: Macrochelidae) - Niogret, Jerome; Nicot, Antoine; de Stordeur, Eric; Bertrand, Michel (Zootaxa, 2007)
Macrocheles seraphim sp. nov. is described from French and Moroccan populations. This species was found phoretic on three species of dung beetles: Scarabaeus laticollis, Geotrupes mutator and G. spiniger. It was identified on the basis of morphological characters as belonging to the M. glaber group, but also has similarities with M. muscaedomesticae. Its systematic position as investigated by genetic analyses using the ITS-1 marker showed that this species was closely related to M. muscaedomesticae. Its relationship with glaber group species is discussed.